On the fossil Remains of Panochthus Burmeister, 1866 (Xenarthra, Cingulata, Glyptodontidae) from the Pleistocene of southern Brazil - Ferreira,José D. (2015)
The genus Panochthus represents the last lineage of "Panochthini" recorded in the Pleistocene. This genus has a wide latitudinal distribution in South America, and in Brazil it occurs in the southern and northeastern regions. In this paper we describe new material (isolated osteoderms and caudal tube fragments) assigned to Panochthus from the state of Rio Grande do Sul (southern Brazil) and discuss some taxonomic issues related to Panochthus tuberculatus and Panochthus greslebini based on this material . The occurrence of P. greslebini is the first for outside the Brazilian Intertropical Region. In addition, we describe new diagnostic features to differentiate the osteoderms of P. greslebini and P. tuberculatus. Unfortunately, it was not possible to identify some osteoderms at the species level. Interestingly, they showed four distinct morphotypes characterized by their external morphology, and thus were attributed to Panochthus sp. Lastly, we conclude that in addition to P.tuberculatus registered to southern Brazil, there is another species of the genus, assignable to P. cf. P. greslebini. Our analysis reinforce the reliability of caudal tube characters for the classification of species of Panochthus.